Local Wisdom Values in Turun karai Tradition in Sibuluan Nalambok Village, Central Tapanuli Regency, North Sumatra Province - Wahyu Novita Panggabean; Endrizal; Emzia Fajri (Kirana Publisher (KNPub), 2024)
The research entitled